Pengaruh Pemanfaatan Tempurung Kelapa sebagai Material Serat terhadap Kuat Tekan dan Kuat Tarik Beton - Rustendi, Iwan (Department of Civil Engineering, Diponegoro University, 2004)
Concrete is the one of building material that excisting intense very popular in engineering and contractor as well as in general society. To complete the performance of concrete, several inovation have already made by people that have competen of its. Consider of result from detailed test, material addition that capable to increasing strength of concrete is fiber. Addition fiber for concrete will make great influence for tensile strength of concrete, but for compressive strength is not significan. In this research, will detected how much that influence of coconut shell fiber toward strength from several variation dosis. Sample of concrete is made in four type, first sample with 0% of coconut shell fiber, second sample with 5% of coconut shell fiber, third sample with 10% of coconut shell fiber and the last sample with 15% of coconut shell fiber. From result of detailed test concrete, the compressive strength is to be reduction, but the tensile strength to be increase alowed from increasing coconut shell fiber. With 5% addition of coconut shell fiber the compressive strength is reducted at 19,36% and the tensile strength is increasing at 4,29%, with 10% addition of coconut shell fiber the compressive strength is reducted at 23,00% and the tensile strength is increasing at 19,63% and with 15% addition of coconut shell fiber the compressive strength is reducted at 40,09% and the tensile strength increasing at 36,81%. Key words : fiber concrete, coconut shell fiber, compressive strength, tensile strength.